IBM PowerHA SystemMirror 7.2.1 for IBM AIX updates - Quintero, Dino (IBM redbooks., 2017)
Abstract This IBM® Redbooks® publication helps strengthen the position of the IBM PowerHA® SystemMirror® solution with a well-defined and documented deployment models within an IBM Power Systems™ virtualized environment, which provides customers with a planned foundation for business resilience and disaster recovery for their IBM Power Systems infrastructure solutions. This publication addresses topics to help meet customers' complex high availability and disaster recovery requirements on IBM Power Systems servers to help maximize their systems' availability and resources, and provide technical documentation to transfer the how-to-skills to users and support teams. This book is targeted at technical professionals (consultants, technical support staff, IT Architects, and IT Specialists) who are responsible for providing high availability and disaster recovery solutions and support with IBM PowerHA SystemMirror Standard and Enterprise Editions on IBM Power Systems servers.